Pelaksanaan Restitusi Bagi Anak Korban Tindak Pidana Pencabulan - Sinda Rahmawati (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2024)
Children are individuals who are vulnerable to becoming victims of criminal acts that require protection. One form of protection for child victims as an effort to fulfill the rights of victims is the granting of restitution rights. The purpose of conducting this legal research is to find out the implementation and obstacles in granting restitution to District Court of Tanjungkarang case number 29/Pid.Sus-Anak/2022/PN Tjk. This research is normative legal research that is prescriptive and applied based on statue approach and case approach. This research employed the data collection technique of literature studies and interviews as research support. The result of the research showed that children who were victims in this case has not received protection in the form of fulfilling the right to restitution even though the defendant has been found guilty of committing the crime of obscenity by the judge. This is due to delays in submitting requests for restitution by the victim's child. So that the victim's child can only reapply for restitution after receiving a court decision that has permanent legal force through a civil lawsuit. However, considering that the filing procedure requires a lot of time, this has become an obstacle to fulfilling the right of restitution for child victims. As a result, can influence implementation of restitution for child victims of abuse in this case.